INVESTIGATION OF ARRHENIUS-CONTROLLED CHEMICAL REACTION THROUGH A SUPERHYDROPHOBIC MICROCHANNEL (FUDMA JOURNAL OF SCIENCES, 2023)
The consequence of fully developed free convection with Arrhenius-controlled heat flow for a viscous and an electrically-conducting fluid flowing along an isothermally heated vertical parallel plate in a slit micro-channel is presented in this article. One wall had super-hydrophobic slip (SHS) and a temperature spike, while the other did not. A semi-analytical technique (perturbation series) was utilized to analyze the primary equations. The analytical solutions were thoroughly presented, and the functions of the pertinent parameters were illustrated with the help of various plots. It is revealed from this work that the action of chemically reacting factors is noticed to substantially strengthen the fluid movement in the micro-channel for a constant pressure gradient. In the fields of engineering and medicine, it is essential to understand these fluids' characteristics. Due to the lubrication of micro-channel boundary walls where conductivity and viscosity interact with thermos-physical behavior, the outcomes of the current research can substantially enhance the operations of micro-electro-mechanical systems (MEMS) and micro-devices that rely on micro-fabrication processes.
Keywords: Arrhenius-controlled fluid; free convection; super-hydrophobic slip; temperature jump; slit micro-channel